Children's book in Siberia: a historiographic review - E. V. Engalycheva (Библиосфера, 2017)
The article is devoted to the history of Siberian regional children's book publishing. The author has collected theoretic-practical opinions of historians, bibliologists, publishers and booksellers, librarians and bibliographers, psychologists and sociologists, which purpose is to generalize and reveal regularities of books' flow for children. V. G. Belinsky, L. N. Tolstoy, F. G. Tol’, N. V. Chekhov developed the first concepts of children's book. N. K. Krupskaya, V. A. Sukhomlinsky studied the «core» of the children book repertoire. V. G. Sopikov, B. S. Bondarsky reviewed children's literature of the 19th century in their bibliographic works. The author allocated some organizational components using formal-logical, comparative-historical and structural-typological methods. The first block is related to studying such definitions as «children's book», «children's literature», «editions for children», «a circle of childhood reading», «the repertoire of children's books», their typological signs. The presented concepts are investigated according to tasks, which children's editions solve. S. G. Antonova and S. A. Karaichentseva touched issues of children's literature typology in their publications. The second block of literature reveals the children's book development in Russia in various periods of its formation. I. E. Barenbaum, A. A. Grechikhin, A. A. Belovitskaya studied general fundamentals of the book's history, while A. Ivich, L. Kohn, I. Lupanova considered the history of children’s books. The third block is devoted to printing and art features of the children's book design, activity of universal and specialized publishing houses to distribute literature for children. The fourth block explains such category as «reader - library», considers techniques of work with children's book, offers methodical recommendations for teachers and tutors. Readers’ activity is examined as well. The author analyzes interests, factors, incentives and aims influencing childhood reading. Dissertation researches disclose the regional specifics of children's book publishing in 1980-2013, confirm the considered subject relevance. The historical, comparative, formal and logical analysis carried out by the author will be useful both the specialists in publishing and editorial affairs, researchers studying the history and development of the children's book, historians, and teachers in the educational process of such courses as «Publishing and Editing», «Children's Literature», «Book Science». The author concludes that the children's book has been studied in different periods of its development in the context of numerous aspects, directions and components, which makes it possible to reveal the special patterns of its existence.